2008
DOI: 10.1177/147323000803600217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Telomerase Activity on Carcinogenesis and Survival in Laryngeal Carcinoma

Abstract: This study aimed to look at whether a correlation exists between telomerase activity and survival of laryngeal carcinoma patients. Telomerase activity was measured by telomerase repeat amplification protocol in 31 laryngeal carcinomas and adjacent normal tissues, and in 21 vocal cord polyps (controls). Follow-up was for at least 60 months. Telomerase activity in tissues adjacent to laryngeal carcinomas was significantly higher than in the carcinomas which was, in turn, significantly higher than in vocal cord p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Several studies have, indeed, reported that TERT mRNA levels and telomerase activity are higher in poorly differentiated SCC [ 63 , 126 , 143 , 146 , 166 – 169 ], increase with tumor stage [ 63 , 131 , 142 , 166 ], and are associated with lymph node involvement [ 63 , 126 , 131 , 137 , 139 , 170 ] or extracapsular extension of lymph node metastases [ 125 ]. Numerous studies have analyzed telomerase’s ability to predict outcome (Table 1 ) [ 46 , 63 , 125 , 127 , 130 , 136 , 139 , 140 , 144 , 171 177 ], and most have reported a correlation between increased telomerase expression and activity and a reduced response to treatment and a higher rate of regional and distant metastases ultimately resulting in poor clinical outcome [ 63 , 125 , 127 , 136 , 144 , 171 , 173 176 ]. A study examining a large sample of neoplastic tissues from 217 HNSCC patients reported that telomerase activity was an independent predictor of poor survival after adjustment was made for age, site, stage, histological grade, tumor depth, and extracapsular extension [ 125 ].…”
Section: Telomerase In Hnsccmentioning
confidence: 99%
“…Several studies have, indeed, reported that TERT mRNA levels and telomerase activity are higher in poorly differentiated SCC [ 63 , 126 , 143 , 146 , 166 – 169 ], increase with tumor stage [ 63 , 131 , 142 , 166 ], and are associated with lymph node involvement [ 63 , 126 , 131 , 137 , 139 , 170 ] or extracapsular extension of lymph node metastases [ 125 ]. Numerous studies have analyzed telomerase’s ability to predict outcome (Table 1 ) [ 46 , 63 , 125 , 127 , 130 , 136 , 139 , 140 , 144 , 171 177 ], and most have reported a correlation between increased telomerase expression and activity and a reduced response to treatment and a higher rate of regional and distant metastases ultimately resulting in poor clinical outcome [ 63 , 125 , 127 , 136 , 144 , 171 , 173 176 ]. A study examining a large sample of neoplastic tissues from 217 HNSCC patients reported that telomerase activity was an independent predictor of poor survival after adjustment was made for age, site, stage, histological grade, tumor depth, and extracapsular extension [ 125 ].…”
Section: Telomerase In Hnsccmentioning
confidence: 99%
“…Due to the development of molecular biology techniques, the latest research on the diagnosis of cancer diseases, including laryngeal cancer, has been focused on the occurrence of a specific type of molecular pattern. The molecular patterns detected in the development of head and neck cancers, including laryngeal cancer, include molecules such as epidermal growth factor receptor (EGFR) [2][3][4] telomerase activity [5], overexpression and amplification of cyclin D1 genes (CCND1) [6], cathepsin D [7], type II estrogen binding sites (EBS) [8], S100-A2 Ca2+ binding proteins [9], type 2 cyclo-oxygenase (Cox-2) [10,11], and galectin-3 [12,13]. As reported in the literature, many scientists have also noted the participation of some viruses in the development of laryngeal cancer, including infection with oncogenic human papillomavirus (HPV), human alphaherpesvirus 1 (HHV-1) [14], and Epstein-Barr Virus (EBV) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on HNSCC have shown that telomere attrition [18][19][20][21][22][23][24][25] and telomerase activation [18,20,22,[26][27][28][29][30][31][32][33][34][35] are frequent events in this malignancy. However, several studies have analyzed only small numbers of patients, few studies have evaluated both telomere length and telomerase activation in the same samples [18][19][20][21][22]34], and only two research groups have examined matched tumoral and adjacent tissues [22,34].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have analyzed only small numbers of patients, few studies have evaluated both telomere length and telomerase activation in the same samples [18][19][20][21][22]34], and only two research groups have examined matched tumoral and adjacent tissues [22,34]. Few studies have evaluated the relationship between telomere length/telomerase activation and clinical outcomes [20,[31][32][33], and no studies have analyzed the significance of telomere and telomerase as markers of field cancerization in HNSCC.…”
Section: Introductionmentioning
confidence: 99%